The spinster’s bad faith and misdirection strategies in Catherine Lim’s The English Language Teacher’s Secret - Mohd Nor, Nabilah; Talif, Rosli; Mani, Manimangai (Universiti Putra Malaysia Press, 2017)
Catherine Lim’s The English Language Teacher’s Secret (1987) features Sylvie Ponniah as a spinster during The Graduate Woman phenomenon in Singapore during the mid 1980s. While unaffected by the government’s matchmaking efforts and the excitement of the people around her, the story revealed Sylvie’s secret love story and how she had faithfully held onto the memory for twenty years without having her feelings actually reciprocated at the present time. Lim brilliantly projects the issue of feminism, freedom and individual choice within her spinster narrative, opening up possibilities for Sylvie to be read under an existentialist point of view. By using the conceptual framework that highlights the construction of Sartre’s bad faith, this paper aims to dissect Sylvie’s use of misdirection strategies to evade her freedom. The construction of Sylvie’s bad faith is unrevelled by exploring her secret devotion towards Dr. Chellam, her past lover that she could not marry due to her father’s disapproval. The paper hopes to generate a balanced view upon the spinster, so that her individuality and existential freedom receives equivalent attention; as received by many efforts to record the traits of spinsterhood in fiction.